Pengetahuan dan Sikap Masyarakat serta Peran Petugas Kesehatan Terkait Pencegahan Demam Berdarah Dengue (DBD) - Maria A.L Dawe; Petrus Romeo; Enjelita Ndoen (Journal of Health and Behavioral Science, 2020)
Dengue Hemorrhagic Fever (DHF) is an endemic disease commonly found in tropical and subtropical regions. Community behavior and the role of health workers in DHF prevention significantly influence DHF incidence. This study purposed to determine the relationship between community knowledge and attitude and the role of health workers with DHF prevention in the working area of the Bakunase Public Health Center in 2020. The study design was descriptive-analytic with a cross-sectional study approach. The research sample was 99 respondents, taken by simple random sampling technique. Analysis of research data used the chi-square test. The results showed that knowledge (p = 0.003), attitude (p = 0.000), and the role of health workers (p = 0.004) were related to DHF prevention. Most respondents had poor knowledge but showed a positive attitude towards DHF prevention. Intensive counseling on DHF prevention is essential to ensure active community participation in DHF prevention activities.